2008
DOI: 10.1007/s00216-008-2510-1
|View full text |Cite
|
Sign up to set email alerts
|

A method for the quantification of biomarkers of exposure to acrylonitrile and 1,3-butadiene in human urine by column-switching liquid chromatography–tandem mass spectrometry

Abstract: 1,3-Butadiene and acrylonitrile are important industrial chemicals that have a high production volume and are ubiquitous environmental pollutants. The urinary mercapturic acids of 1,3-butadiene and acrylonitrile-N-acetyl-S-(3,4-dihydroxybutyl)cysteine (DHBMA) and MHBMA (an isomeric mixture of N-acetyl-S-((1-hydroxymethyl)-2-propenyl)cysteine and N-acetyl-S-((2-hydroxymethyl)-3-propenyl)cysteine) for the former and N-acetyl-S-2-cyanoethylcysteine (CEMA) for the latter-are specific biomarkers for the determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 24 publications
9
41
0
7
Order By: Relevance
“…Moreover, our data confirm recent findings showing significant differences between smokers and non-smokers for AAMA [22], GAMA [34], 2-HPMA [22], 3-HPMA [22], AMCC [22], CEMA [21], SPMA [7], HMPMA [33], and 1-/2-MHBMA [24]. In accordance with the literature, for DHBMA, similar concentrations in smokers and nonsmokers were observed [21,27].…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Moreover, our data confirm recent findings showing significant differences between smokers and non-smokers for AAMA [22], GAMA [34], 2-HPMA [22], 3-HPMA [22], AMCC [22], CEMA [21], SPMA [7], HMPMA [33], and 1-/2-MHBMA [24]. In accordance with the literature, for DHBMA, similar concentrations in smokers and nonsmokers were observed [21,27].…”
Section: Discussionsupporting
confidence: 95%
“…In accordance with the literature, for DHBMA, similar concentrations in smokers and nonsmokers were observed [21,27]. On the one hand, DHBMA may be formed from endogenous butadiene-diol [35]; on the other hand, there are other exogenous sources apart from 1,3-butadiene, namely 2-chloroprene and epichlorohydrine, two chemicals mainly used in polymer synthesis [36].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is reported that the high organic content of the solvent may significantly increase the sensitivity in ESI-MS detection [34,35]. In comparison to common RP-columns [17,24,36] best peak shapes, highest intensities and a significantly better separation from urinary interferences for the studied mercapturic acids were obtained on a HILIC column. Retention of the analytes on a HILIC column is strongly dependent on chromatographic conditions like the level of acetonitrile in mobile phase, used buffer-type, its concentration and pH-value.…”
Section: Chromatographymentioning
confidence: 81%
“…1). Schettgen et al [36] noticed as well that in human urine samples one MHBMA peak is clearly predominant and they conclude that this might be due to differences between the purchased standard substance and the metabolic in vivo reaction. Ding et al [39] observed similarly only one MHBMA peak in human urine.…”
Section: Application Of the Methodsmentioning
confidence: 95%